2018
DOI: 10.1016/j.jped.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with breastfeeding maintenance for 12 months or more: a systematic review

Abstract: The maintenance of breastfeeding for 12 months or more is associated with multiple factors, emphasizing the contextual factors and those related to some maternal sociodemographic characteristics. Associations differ in effect and magnitude between the different populations studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
50
6
37

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 46 publications
10
50
6
37
Order By: Relevance
“…The same disagreement occurred with the variable maternal occupation, frequently associated with early weaning, given that this practice can be related to women's return to their work activities. (21) The result described in the present study may be explained by the moment of the postpartum period in which women were assisted (around 20 days after childbirth) and the length of paid maternity leave (between four and six months) in Brazil. (8) Regarding level of education, most postpartum women who were performing exclusive breastfeeding studied up to eight years, that is, finished their education at elementary school.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The same disagreement occurred with the variable maternal occupation, frequently associated with early weaning, given that this practice can be related to women's return to their work activities. (21) The result described in the present study may be explained by the moment of the postpartum period in which women were assisted (around 20 days after childbirth) and the length of paid maternity leave (between four and six months) in Brazil. (8) Regarding level of education, most postpartum women who were performing exclusive breastfeeding studied up to eight years, that is, finished their education at elementary school.…”
Section: Discussionmentioning
confidence: 60%
“…Studies reported that early weaning is more common among younger women (< 20 years) than among older women (>30 years). (20,21) This divergence may be explained by the higher number of women undergoing exclusive breastfeeding who had already had a breastfeeding experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gessica et al that the factors with the highest percentages of associations with maintenance of breastfeeding for 12 months or more with normal growth. 12 Schafer et al found in there study that experiencing trouble with baby's latch, problems with milk flow/supply and painful breast-feeding were significantly associated with breast-feeding duration. 13 Gizaw et al found in their study that one hundred eighty eight of the children were fed breast milk exclusively for the first 6 months of age; the rate of EBF in the study area was 74% (95% CI 70, 78%).…”
Section: Discussionmentioning
confidence: 93%